Al-Manhaj Dan Al-Ṭariq Dalam Metodologi Tafsir - Lujeng Lutfiyah; Moh Sahlul Khuluq (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2023)
This study examines the differences between al-manhaj and al-ṭariq in the methodology of interpretation. The research aims to provide a comprehensive understanding of these terms. A literature review approach was employed, analyzing relevant scholarly sources on the topic. Content analysis was conducted to compare the definitions and usage of al-manhaj and al-ṭariq in various tafsir works. The findings reveal that although al-manhaj and al-ṭariq have distinct appearances, they share the fundamental meaning of being methods or approaches to achieve a goal. However, their usage and emphasis differ in the field of tafsir methodology. Al-manhaj is closely related to the writing style, interpretive school, and general form of interpretation adopted by a mufassir and their tafsir book. On the other hand, al-ṭariq pertains to the research methods and steps used as a practical implementation of the manhaj. This research contributes to a deeper understanding of the nuanced differences between al-manhaj and al-ṭariq in tafsir methodology. It highlights the importance of considering these terms in the field of interpretation. By clarifying their meanings and usage, this study provides valuable insights for scholars and researchers in the field of tafsir. It serves as a foundation for further exploration and discussion on the topic, ultimately enhancing the knowledge and understanding of tafsir methodology.